Assessing labour market and supply chains disruptions during Covid-19 in Malaysia - Hamzah, Heizlyn Amyneina (2022)
The unprecedented global outbreak of COVID-19 has triggered severe impacts on the economy in Malaysia. Unlike previous crises, the COVID-19 crisis has induced disruption on both the supply and demand sides. The economic fallout due to COVID-19 has increased unemployment rates in the labour market. This labour market disruption has translated into a rise in the loss of employment. The measures taken in curbing the spread of the COVID-19 pandemic have also significantly reduced the operating capacity of the businesses. This reduction in operating capacity has created a massive disruption in the supply chain. The disruption on both sides of the economy calls for an economy-wide assessment of the impacts of COVID-19 in Malaysia. Thus, the first objective of this work is to investigate the impacts of the labour market and supply chain disruption on the economy. The prolonged implementation of non-pharmaceutical interventions (NPI) that involve all sectors of the economy incurred high losses to the economy. In the future, sectors such as Agriculture and Mining and Quarrying that play a significant role in the supply chain should be prioritised and excluded from the measures. Hence, we have undertaken an analysis to determine the key sectors of the labour market and production. The determination of key sectors also provides information on the speed at which the impacts of disruption propagate from one sector to another. In achieving the first objective, the extended input-output modelling technique is utilised. This modelling technique is considered novel in that the model extended to integrate the real-time administrative data, Loss of Employment (LOE). The second objective is fulfilled by using the average propagation length (APL) technique. The APL technique assesses the forward and backward linkages of an economic sector and is built on the standard Leontief input-output matrix. The impacts of LOE due to the outbreak of COVID-19 on the economy are relatively small but the impacts of COVID-19 are significant when taking into consideration both the LOE and supply chain shocks. In the determination of key sectors, labour intensity plays a significant role. Visualisation of the production chain shows that the Manufacturing sector dominates the supply chain. Policy makers must identify the key sectors in the economy that should be excluded or lifted from the implementation of non-pharmaceutical interventions (NPIs). The current policy regarding the closure of the economy due to COVID-19 pandemic formulated by the Malaysian National Security Council (NSC) is inclined towards considering the health crisis impact over the economic crisis. Therefore, it is time for policymakers to consider this modelling as part of a supporting tool in evidence-based analysis to facilitate decision-making.